(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
Currently, the development of modern drugs leads to many problems, including drug ineffectiveness, immunogenetic problems, and disruption of cytotoxicity and metabolic processes. These limitations limit its use in various systems. As a natural resource, microalgae are rich not only in bioactive compounds but also in many biological properties, such as richness in active compounds, high photosynthetic ability, as well as biocompatibility for the human body. These properties allow the use of microalgae as targeted medicines. It also creates great opportunities for the diagnosis and treatment of various promising diseases. Therefore, information is provided on the use of microalgae as medicines and the optimization of their quality.